CRISPR/Cas9‐mediated Knockout of SIRT6 Imparts Remarkable Antiproliferative Response in Human Melanoma Cells in vitro and in vivo. (24th July 2020) - Garcia‐Peterson, Liz M.; Ndiaye, Mary A.; Chhabra, Gagan; Singh, Chandra K.; Guzmán‐Pérez, Glorimar; Iczkowski, Kenneth A.; Ahmad, Nihal
Abstract: Melanoma is one of the most aggressive, potentially fatal forms of skin cancer and has been shown to be associated with solar ultraviolet radiation‐dependent initiation and progression. Despite remarkable recent advances with targeted and immune therapeutics, lasting and recurrence‐free survival remain significant concerns. Therefore, additional novel mechanism‐based approaches are needed for effective melanoma management. The sirtuin SIRT6 appears to have a pro‐proliferative function in melanocytic cells. In this study, we determined the effects of genetic manipulation of SIRT6 in human melanoma cells, in vitro and in vivo . Our data demonstrated that CRISPR/Cas9‐mediated knockout (KO) of SIRT6 in A375 melanoma cells resulted in a significant (1) decrease in growth, viability and clonogenic survival and (2) induction of G1‐phase cell cycle arrest. Further, employing a RT 2 Profiler PCR array containing 84 key transformation and tumorigenesis genes, we found that SIRT6 KO resulted in modulation of genes involved in angiogenesis, apoptosis, cellular senescence, epithelial‐to‐mesenchymal transition, hypoxia signaling and telomere maintenance. Finally, we found significantly decreased tumorigenicity of SIRT6 KO A375 cells in athymic nude mice. Our data provide strong evidence that SIRT6 promotes melanoma cell survival, both in vitro and in vivo, and could be exploited as a target for melanoma management. Abstract : SIRT6 has been shown to act as a tumor promoter or suppressor depending on the cancer type. This study supports the tumor promoter role of SIRT6 in melanoma, one of the deadliest forms of UV‐related skin cancers. We found CRISPR/Cas9‐mediated SIRT6 knockout (KO) imparted marked antiproliferative effects in human melanoma cells in vitro and antitumorigenic response in vivo . Additionally, we found SIRT6 KO significantly affected several cancer‐associated pathways, including apoptosis, cellular senescence and epithelial‐to‐mesenchymal transition, suggesting SIRT6 has an important role in melanoma progression. Thus, SIRT6 inhibitory approaches could potentially be used in melanoma management and should be explored further.